Percepções dos servidores sobre responsabilidade social em unidades de extensão da Universidade Federal do Pará - HORTA, Luiza Cristilene da Costa (Universidade Federal do Pará, 2018)
The main objective of this work is to identify the perceptions of servers of the Dentistry Clinic, Psychology Clinic and Legal Practice Center as far as the social responsibility of UFPA. The specific objectives are: 1) discuss conceptually social responsibility in the public sector, 2) describe the services provided by the units that provide services to the surrounding community, and 3) to verify how these actions are perceived and evaluated by the servers, based on the dimensions of social and environmental responsibility.The referential presents concepts of social and environmental practices, conceptions of social responsibility of ABNT NBR IS0 26000 and the Ethos Institute of Social Responsibility, discusses the insertion of social responsibility in public administration, especially in universities, considering their contributions to sustainable development. The analysis approach is qualitative, consisting of bibliographical research, documentary survey and field research. The researchactors are servrsof Núcleo de Prática Jurídica da UFPA, da Clínica de Psicologia e da Clínica de Odontologia, departmentsof UFPA, thatprovideservicestothecommunity. Interviews were conducted, with Instruments based on the dimensions of the Social Responsibility of Ethos Institute. The results indicate positive perceptions of servers about organizational social responsibility, expressing general views about mission, vision and institutional values, job satisfaction and identifying the social commitment of the actions performed. In contrast, some obstacles to the strengthening of socio-environmental commitments were evidenced as the need to improve thes public participation process, transparency and environmental education. Some difficulties related to problems with physical and budgetary structure do not compromise the identification of the actors interviewed with the objectives of the Units and do not weaken the image on institutional social responsibility.